Rehabilitation of the visually impaired: opinions and expectations regarding individual limitations and the "Waiting-Group" - Rita de Cassia letto Montilha; Maria Inés Rubo de Souza Nobre; José Newton Kara; Edméa Rita Temporini (Colegio Colombiano de Terapia Ocupacional, 2001)
This study searches out limitations and expectations of visually impaired customers attended to in a university service (CEPRE) in Campinas, State of Sao Paulo, Brazil, from 1994 to 1997, in order to get subsidies for improving the quality of the services offered. A special type of attendance called "waiting-group" is described with the customers' opinions regarding this kind of attendance being also surveyed during the rehabilitation process. Twenty subjects, aged 12 and more, with vision impairment, either congenital or acquired, compound the study sample. A questionnaire, employed for data collecting, disclosed: a slight predominance of males (57.0%); average age equal to 32.2; the majority ofthe subjects are acquainted with the rehabilitation approach, presenting expectations as to the work developed by the service; among the opinions regarding limitations due to vision impairment, those associated with locomotion (80.0%) and ability to exercise professional activities (75.0%) predominate; as to personal changes that came about as a result of taking part in the "waiting-group", that of the acceptance of the vision impairment prevails (89.5%). Concluding, the Authors stress the need for vision rehabilitation programs to promptly attend the demand, in a mandatory way, taking into account both the customers'needs and opinions.